(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The problem of research was to identify after the use of cost technology based on specifications in the validity of determining and measuring the costs of the implementation of contracting, by applying to al-Mansour General Construction Contracting Company as an appropriate alternative to the traditional costing system currently adopted, which is characterized by many shortcomings and weaknesses Which has been reflected in the validity and integrity of the calculations. To solve this problem, the research was based on the premise that: (The application of cost technology based on specifications will result in calculating the cost of the product according to the specification required by the customer, to meet his wishes properly and without any waste and loss of costs). The research a set of conclusions and recommendations, perhaps the most important of which is that the application of (ABCII )technology in the implementation of contracting contracts helped to reduce the cost of the product (apartment), and this reduction will provide a vision of the company for the importance of the specification in determining the cost of products desired by the customer, as well as determining the citizen Excessive cost to be processed leading to staying in the market and achieving a competitive advantage, and based on the results of the research the researcher recommends the need to adopt cost technology based on specifications, because it provides correct and complete information to help to make strategic decisions that enable the company to Sovereignty in the competition market for contracting.